2007
DOI: 10.1002/lsm.20472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the multiple pass, low fluence algorithm for radiofrequency tightening of the lower face

Abstract: The low-fluence, multiple pass technique is an effective algorithm for radiofrequency skin tightening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 5 publications
2
56
0
2
Order By: Relevance
“…Monopolar RF is the first nonablative RF technology shown to be effective for skin tightening [24,25]. The original monopolar RF protocols, using single-pass, high fluence regimen, were associated with a greater degree of discomfort and complications, including tissue irregularity and burns [24].…”
Section: Discussionmentioning
confidence: 99%
“…Monopolar RF is the first nonablative RF technology shown to be effective for skin tightening [24,25]. The original monopolar RF protocols, using single-pass, high fluence regimen, were associated with a greater degree of discomfort and complications, including tissue irregularity and burns [24].…”
Section: Discussionmentioning
confidence: 99%
“…A new treatment protocol that uses a multipass, low fluence regimen has been developed with the aim to reduce the discomfort of patients and the risk of adverse effects. A recent study indicated that this new treatment protocol is effective [4]. However, there are several issues concerning the use of monopolar radiofrequency for skin tightening.…”
Section: Discussionmentioning
confidence: 99%
“…This may further explain the discrepancy between our findings and those of the previous study in which three treatments were given. More recently, the Leal laxity classification system has been used to assess the efficacy of the monopolar radiofrequency device [4]. Although this classification allows better assessment of the degree of skin laxity, interobserver and intraobserver variations still exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, improvement in skin tightening lasts more than 6 months [15]. The MFR device inserts a microneedle into the dermis and directly delivers thermal energy.…”
Section: Discussionmentioning
confidence: 99%